Foamed nickel-based composite material based on electro-deposition / hydrothermal synthesis method and preparation method of foamed nickel-based composite material

By electrodepositing cobalt hydroxide on nickel foam and converting it into ZIF-67, and then hydrothermally preparing NiCo-LDH, the agglomeration and uneven loading problems of LDH and MOFs materials were solved, high specific capacitance and mechanically stable supercapacitor materials were achieved, and the preparation process was simplified.

CN120674242APending Publication Date: 2025-09-19GUILIN UNIV OF ELECTRONIC TECH

Patent Information

Application Number
CN202510833264.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-20
Publication Date
2025-09-19

AI Technical Summary

Technical Problem

In the existing technology, LDH and MOFs materials have agglomeration problems in supercapacitors, resulting in structural instability and affecting ion and electron transmission. When binders are used, the active sites are covered, hindering the contact between the electrolyte and the active material. The hydrothermal method and electrodeposition method each have problems of uneven loading or low mechanical stability.

Method used

Cobalt hydroxide was loaded on nickel foam by electrodeposition and converted into ZIF-67. NiCo-LDH was then prepared by hydrothermal method to form a uniformly loaded NiCo-LDH@Co(OH)2/NF composite structure, avoiding agglomeration and the use of binders. The preparation process was simplified by combining electrodeposition and hydrothermal method.

Benefits of technology

High specific capacitance performance and mechanical stability are achieved. The material still maintains 70-80% of its initial capacity after 5,000 charge and discharge cycles, significantly improving the electrochemical performance and cycle stability and shortening the preparation time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120674242A_ABST
    Figure CN120674242A_ABST
Patent Text Reader

Abstract

The invention discloses a foamed nickel-based composite material based on an electro-deposition / hydrothermal synthesis method, which is characterized in that firstly, foamed nickel NF is used as a substrate, cobalt hydroxide is loaded on the surface of the NF through electro-deposition, and Co (OH) 2 / NF with a lamellar stacked flower-shaped structure is obtained; the preparation method comprises the following steps: preparing NiCo-LDH (layered double hydroxide) Co (OH) 2 / NF, then converting the NiCo-LDH (layered double hydroxide) Co (OH) 2 / NF into ZIF-67 through an impregnation method to obtain ZIF-67 (at) Co (OH) 2 / NF with a regular dodecahedron structure, and finally, preparing NiCo-LDH (at) Co (OH) 2 / NF with a honeycomb stacked structure through a hydrothermal method. The preparation method comprises the following steps: 1, preparing foamed nickel electro-deposition cobalt hydroxide; 2, preparing the foamed nickel loaded ZIF67 and cobalt hydroxide; and 3, preparing the nickel foam loaded nickel-cobalt layered double-metal hydroxide and cobalt hydroxide. When the material is used as a supercapacitor material, the area specific capacitance is 17-18F cm <-2 > when the current density is 1mA cm <-2 >; and when the current density is 10mAcm <-2 >, 70-80% of the initial capacity is still kept after 5000 charge-discharge cycles are carried out.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of supercapacitors, and in particular to a foamed nickel-based composite material based on an electrodeposition / hydrothermal comprehensive method and a preparation method thereof. Background Art

[0002] Common materials in supercapacitor materials include metal organic framework materials MOFs, layered double hydroxide (LDH), carbon materials, conductive polymers and transition metal compounds.

[0003] LDH has a high specific surface area and abundant ion insertion sites, and therefore has a high theoretical specific capacitance. However, common LDHs represented by NiCo-LDH, CoAl-LDH and NiMo-LDH are all in powder form. Therefore, LDH has the characteristics of agglomeration tendency and structural instability, which leads to structural changes in LDH during the charge and discharge process, thereby hindering the transmission of ions and electrons, and ultimately causing LDH to have cyclic stability problems.

[0004] MOFs have high energy storage capacity due to their diverse scaffold structures, scalable pore sizes, large specific surface areas, and abundant metal redox sites. At the same time, MOFs have specialized interconnected pores that enable effective electrolyte filtration, thereby shortening the diffusion path of electrolyte ions and achieving rapid kinetic response. However, common MOFs such as ZIF-8, ZIF-67, MIL-177, and MIL-125 have small particle sizes. Therefore, MOFs materials also have agglomeration problems during the preparation process, resulting in a reduction in the specific surface area of ​​the MOFs material, the masking of internal active sites, and poor contact between particles, forming a discontinuous conductive network, which ultimately affects the electrochemical performance of the MOFs material.

[0005] From the above analysis, it can be seen that both LDH and MOFs have agglomeration problems. The agglomeration problem can be solved by loading the powder material onto the carrier. For example, the existing document 1 (Prabhu S, Sohila S, Navaneethan D, et al. Three dimensional flower-like CuO / Co3O4 / r-GO heterostructure for high-performance asymmetric supercapacitors [J]. Journal of Alloys and Compounds, 2020, 846: 156439.) A new three-dimensional flower-like CuO / Co3O4 / r-GO heterostructure was synthesized by a hydrothermal method. The prepared three-dimensional flower-like CuO / Co3O4 / r-GO heterostructure has a high specific surface area, provides a large interface contact area between the electrode and the electrolyte solution, provides fast surface reaction kinetics and improved conductivity, thereby achieving significant electrochemical performance. Although r-GO has a large specific surface area and can provide more active sites for electrochemical reactions, the two-dimensional layered structure can provide good dispersibility and inhibit the agglomeration of active materials. However, since the obtained material is still in powder form, a binder needs to be used during the tableting or coating process, which leads to the problem that the binder covers part of the active sites and hinders the contact between the electrolyte and the active material.

[0006] In order to solve the problem of binder, the inventor of the present invention conducted preliminary work by directly loading it onto bulk material using hydrothermal method or electrodeposition method. Utilizing the characteristics of bulk material itself with a large three-dimensional skeleton structure, the powder material is loaded to avoid the agglomeration problem. At the same time, in principle, the subsequent use of binder is avoided. Specifically, existing document 2 (Prabakaran P, Prabhu S, Selvaraj M, et al. Design and preparation of NiCoS nanostructures on Ni foam for high-performance asymmetric supercapacitor application [J]. Journal of Materials Science: Materials in Electronics, 2022: 1-13.) A one-pot in-situ hydrothermal method is used to prepare NiCoS nanostructures on nickel foam. The prepared NiCoS / NF-100 is at 1mAcm -2 At a current density of 3.3 F cm -2Although this method is simple to prepare and only requires one step of hydrothermal treatment, the hydrothermal method can produce NiCoS / NF-100 with uneven morphology, which leads to a large local loading on the nickel foam.

[0007] In order to solve the above-mentioned problem of uneven loading on the nickel foam skeleton, it can be improved by electrodeposition. For example, the existing literature 3 (Evariste U, Jiang G, Yu B, et al. One-step electrodeposition of molybdenum nickel cobalt sulfides on ni foam for high-performance asymmetric supercapacitors [J]. Journal of Energy Storage, 2020, 29: 101419.) uses a one-step electrodeposition method to prepare MoNiCoS microspheres on nickel foam. The MoNiCoS@NF electrode has a high capacitance at 0.5A g -1 The current density was as high as 1472F g -1 The specific capacitance of the MoNiCoS@NF electrode is as high as 98% after 5000 charge-discharge cycles. The porous structure and nanometer size of the MoNiCoS microspheres obtained by this technical solution facilitate rapid ion transport and charge transfer, thereby improving the electrochemical performance. This technical solution can only form a loose morphology on nickel foam by electrodeposition. Although it can improve uniformity, the mechanical stability is low, that is, it cannot achieve long-term reaction cycle stability; in particular, under high current density conditions, there is a significant volume expansion phenomenon during the electrodeposition process, which leads to severe internal stress, and ultimately causes the electrode material to crack or peel off, reducing the mechanical stability and cycle stability of the electrode.

[0008] Through the above analysis, it can be seen that the single hydrothermal method and the electrodeposition method have their own technical problems that cannot be solved. Combining the two types of technical solutions can complement each other and solve the above technical problems. For example, the existing document 4 (Cao Y, Wang J, Zhong L, et al. ZnCoS / ZnCoLDH lamellar core-shell materials for high-performance asymmetric supercapacitors[J]. Journal of Energy Storage, 2025, 110: 115250.) uses hydrothermal sulfurization to prepare the ZnCoS skeleton, and electrodeposit ZnCo-LDH nanosheets to form a core-shell structure ZnCoS / ZnCo-LDH composite material. The composite material is then 1A g-1 The current density is 2240F g -1 The specific capacitance of the ZnCoS / ZnCo-LDH-2 electrode is 2.33 W / m, and after 5000 cycles, the ZnCoS / ZnCo-LDH-2 electrode can still maintain 77.9% of the initial capacity. This technical solution uses the ZnCo-LDH layer as a "protective shell" to effectively prevent the volume expansion and structural collapse of ZnCoS during the charge and discharge process. However, when electroplating ZnCo-LDH on the surface of hydrothermally prepared ZnCoS, there is still the aforementioned technical problem of inconsistent ZnCo-LDH thickness on the electrode surface due to uneven hydrothermal distribution of ZnCoS, as well as the problem of local stress concentration caused by the subsequent electroplating method.

[0009] To address the uneven material distribution problem of prior art 4, which results from hydrothermal deposition followed by electrodeposition, the inventors' research team conducted preliminary work by first introducing the precursor onto a conductive substrate using electrodeposition, followed by hydrothermal derivatization to the target material. This approach not only ensures uniform material loading and prevents agglomeration, but also enhances the interaction between the material and the conductive substrate, preventing the shedding of active material during electrochemical testing. Specifically, in existing document 5 (Chen Menglong et al. A nickel foam loaded cobalt sulfide / nickel sulfide NF-CoS / NiS and its preparation method and application: CN120126949A.2025-06-10), the inventors found that cobalt nitrate hexahydrate was first dissolved in deionized water as an electrolyte, and then cobalt hydroxide was electrodeposited using a double electrode. After drying, it was immersed in a 2-methylimidazole solution for 24 hours to derive ZIF-67, which was then vertically placed in a polytetrafluoroethylene reactor filled with thioacetamide solution and sulfurized for 6 hours. Finally, nickel nitrate hexahydrate and thiourea were dissolved in deionized water as an electrolyte and nickel sulfide was electrodeposited using a three-electrode. After electrochemical testing, the area specific capacitance of NF-CoS / NiS was 8.2 F cm -2 Although this technical solution solves the agglomeration problem of powder materials by using the method of first electrodeposition and then hydrothermal treatment and avoids the problem of weak bonding caused by structural matching differences due to morphology in the hydrothermal method, the entire preparation process takes 6 days due to the use of a secondary electrodeposition preparation process, which means that there is a technical problem of excessive preparation time. Summary of the Invention

[0010] The purpose of the present invention is to provide a nickel-based foam composite material based on an electrodeposition / hydrothermal comprehensive method and a preparation method thereof. Based on the technical problems existing in the existing document 5, the present invention adopts a method of first electrodepositing cobalt hydroxide on nickel foam and then deriving it into ZIF-67 to achieve uniform and firm distribution of ZIF-67 on the skeleton of nickel foam; finally, hydrothermal etching is adopted to obtain NiCo-LDH. By achieving uniform loading of the precursor and then uniform loading of NiCo-LDH, agglomeration problems are avoided; at the same time, under the premise of avoiding the use of a binder, a strong force is formed between the precursor and the nickel foam; and finally, the preparation time is significantly reduced by half, that is, the invention purpose of simplifying the preparation process is achieved, and the surface capacitance performance is significantly improved.

[0011] In order to achieve the above-mentioned object of the invention, the technical solution adopted by the present invention is:

[0012] A nickel foam-based composite material based on an electrodeposition / hydrothermal method. First, nickel foam NF is used as a substrate, and cobalt hydroxide is loaded on the NF surface by electrodeposition to obtain nickel foam electrodeposited cobalt hydroxide Co(OH)2 / NF. Then, it is converted into ZIF-67 by an impregnation method to obtain nickel foam-loaded ZIF-67@cobalt hydroxide ZIF-67@Co(OH)2 / NF. Finally, a nickel foam-based composite material NiCo-LDH@Co(OH)2 / NF based on the electrodeposition / hydrothermal method is obtained by a hydrothermal method.

[0013] The micromorphology of the Co(OH)2 / NF is a lamellar stacked flower-like structure; the micromorphology of the ZIF-67@Co(OH)2 / NF is a regular dodecahedron structure; and the micromorphology of the NiCo-LDH@Co(OH)2 / NF is a honeycomb stacked structure.

[0014] A method for preparing a foamed nickel-based composite material based on an electrodeposition / hydrothermal combined method comprises the following steps:

[0015] Step 1, preparation of nickel foam electrodeposited cobalt hydroxide, first, dissolving cobalt nitrate hexahydrate in deionized water to obtain electrodeposition solution A, then using a two-electrode system and cyclic voltammetry, with nickel foam NF as the working electrode and a Pt sheet as the counter electrode, to perform electrodeposition under certain conditions, finally, washing the electrodeposited NF with deionized water and then vacuum drying under certain conditions to obtain nickel foam electrodeposited cobalt hydroxide Co(OH)2 / NF;

[0016] In step 1, the conditions for the first electrodeposition are: electrodeposition potential of 5-7V, scan rate of 90-110mVs -1 , the electrodeposition time is 1190-1210s;

[0017] Step 2, preparation of nickel foam loaded with ZIF67 and cobalt hydroxide, first, dissolving 2-methylimidazole in deionized water to obtain an impregnation solution, then impregnating the Co(OH)2 / NF obtained in step 1 in the impregnation solution under certain conditions, finally, washing the impregnated NF with deionized water, and then vacuum drying under certain conditions to obtain nickel foam loaded with ZIF-67 and cobalt hydroxide ZIF-67@Co(OH)2 / NF;

[0018] In step 2, the immersion condition is that the immersion time is 23-25 ​​hours;

[0019] Step 3, preparation of nickel foam-loaded nickel cobalt layered double hydroxide and cobalt hydroxide NiCo-LDH@Co(OH)2. First, nickel nitrate hexahydrate and urea are dissolved in anhydrous ethanol to obtain a hydrothermal reaction solution. Then, under certain conditions, the ZIF-67@Co(OH)2 / NF obtained in step 2 is immersed in the reaction solution for a hydrothermal reaction. Finally, the NF after the reaction is completed is washed with deionized water and then vacuum-dried under certain conditions to obtain nickel foam-loaded nickel cobalt layered double hydroxide and cobalt hydroxide NiCo-LDH@Co(OH)2 / NF.

[0020] In step 3, the hydrothermal conditions are as follows: the ZIF-67@Co(OH)2 / NF is immersed in a vertical manner, the hydrothermal temperature is 130-150°C, and the hydrothermal time is 7-9h;

[0021] In the preparation method, all vacuum drying conditions are: drying temperature is 50-70° C., and drying time is 11-13 h.

[0022] When the obtained nickel foam composite material based on the electrodeposition / hydrothermal method is used as a supercapacitor material, it is charged and discharged in the voltage window range of 0-0.5V and at a current density of 1mA cm -2 When the area specific capacitance is 17-18F cm -2 At a current density of 10 mA cm -2 When the battery is charged and discharged for 5,000 times, it still retains 70-80% of its initial capacity.

[0023] The technical effects of the present invention have been tested and the specific contents are as follows:

[0024] XRD testing of the present invention shows that NiCo-LDH@Co(OH)2 / NF simultaneously has characteristic peaks of NiCo-LDH, ZIF-67 and Co(OH)2, which means that the NiCo-LDH@Co(OH)2 / NF composite structural material has been successfully prepared.

[0025] SEM testing of the present invention shows that the micromorphology of the Co(OH)2 / NF is a lamellar stacked flower-like structure; the micromorphology of the ZIF-67@Co(OH)2 / NF is a regular dodecahedron structure; and the micromorphology of the NiCo-LDH@Co(OH)2 / NF is a honeycomb stacked structure.

[0026] The present invention is tested by three-electrode electrochemical detection. It is known that in 3M KOH solution, the charge and discharge are performed in the window voltage range of 0-0.5V, and the charge and discharge are performed in the window voltage range of 1mA cm -2 At a current density of 1.5 GHz, the area specific capacitance of the NiCo-LDH@Co(OH)2 / NF composite material is 17-18 F cm -2 .

[0027] The present invention has been tested by electrochemical cycling and found that at a current density of 10 mA cm -2 When the NiCo-LDH@Co(OH)2 / NF composite material is charged and discharged for 5000 cycles in the window voltage range of 0-0.5V, it retains 70-80% of the initial specific capacitance.

[0028] The present invention is tested by double-electrode electrochemical detection. It is known that in 3M KOH solution, the NiCo-LDH@Co(OH)2 / NF composite material is charged and discharged at a window voltage of 0-1.6V at 7.99mW cm -2 The power density was 0.382 mWh cm -2 The energy density is 100W, and it still maintains 80.3% of its initial capacity after 5000 charge and discharge cycles.

[0029] Therefore, the present invention has the following advantages over the prior art:

[0030] 1. Based on the high theoretical specific capacitance of nanoflower-shaped NiCo-LDH, combined with the synergistic effect of nanoflower-shaped NiCo-LDH and Co(OH)2 layer stacked flower-like structure, the NiCo-LDH@Co(OH)2 / NF composite material achieves high specific capacitance performance;

[0031] 2. Electrodepositing Co(OH)2 on nickel foam and then in situ growing ZIF-67 solves the problem of insufficient bonding caused by structural morphology differences and achieves uniform distribution of ZIF-67 and NiCo-LDH.

[0032] 3. The composite material is loaded on a conductive substrate nickel foam NF through electrodeposition, which avoids the use of binders and solves the agglomeration problem of powder materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is the XRD test pattern of Example 1;

[0034] Figure 2 This is the SEM test image of Co(OH)2 / NF prepared in Example 1 at 10 μm;

[0035] Figure 3 This is the SEM test image of ZIF-67@Co(OH)2 / NF prepared in Example 1 at 3μm;

[0036] Figure 4 This is the XPS test image of NiCo-LDH@Co(OH)2 / NF prepared in Example 1;

[0037] Figure 5 This is the SEM test image of NiCo-LDH@Co(OH)2 / NF prepared in Example 1 at 1 μm;

[0038] Figure 6 Example 1 at 1 mA cm -2 Charge and discharge curves under current density;

[0039] Figure 7 For Example 1, NiCo-LDH@Co(OH)2 / NF was tested at 10 mA cm -2 Cycling performance diagram after 5000 cycles at the same current density;

[0040] Figure 8 This is the Lagung plot of NiCo-LDH@Co(OH)2 / NF prepared in Example 1;

[0041] Figure 9 This is the XRD test pattern of NiCo-LDH prepared in Comparative Example 1;

[0042] Figure 10 This is the SEM test image of NiCo-LDH prepared in Comparative Example 1 at 1 μm;

[0043] Figure 11 NiCo-LDH prepared in Comparative Example 1 was -2 Charge and discharge curves at different current densities. DETAILED DESCRIPTION

[0044] The present invention is further described in detail through embodiments and in conjunction with the accompanying drawings, but the present invention is not limited thereto.

[0045] Example 1

[0046] A method for preparing a foamed nickel-based composite material based on an electrodeposition / hydrothermal combined method comprises the following steps:

[0047] Step 1: Preparation of cobalt hydroxide electrodeposited on nickel foam. First, 14.15 g of cobalt nitrate hexahydrate was dissolved in 100 mL of deionized water to obtain an electrodeposition solution. Then, a two-electrode system and cyclic voltammetry were used, with nickel foam NF as the working electrode and a Pt sheet as the counter electrode. The electrodeposition potential was 6 V and the scan rate was 100 mV s. -1 , the electrodeposition time is 1200s, and the electrodeposition is carried out. Finally, the electrodeposited NF is washed with deionized water, and then vacuum dried at a drying temperature of 60°C and a drying time of 12h to obtain nickel foam electrodeposited cobalt hydroxide Co(OH)2 / NF;

[0048] In order to prove the composition of Co(OH)2 / NF, XRD test was carried out. The test results are as follows Figure 1 As shown in Figure 3, Co(OH)2 / NF has the characteristic peak of Co(OH)2. The test results show that step 1 successfully loaded Co(OH)2 on the NF surface.

[0049] In order to verify the microstructure of Co(OH)2 / NF, SEM test was carried out. The test results are shown in Figure 2. Figure 2 As shown, combined with the XRD test results, it can be seen that Co(OH)2 with a lamellar stacked flower-like structure is loaded on the surface of the NF skeleton.

[0050] In order to demonstrate the electrochemical performance of Co(OH)2 / NF, the electrochemical performance test was carried out on the Co(OH)2 / NF obtained in step 1. The specific method of the electrochemical performance test was as follows: the electrochemical performance test was carried out in a three-electrode system consisting of the material to be tested as the working electrode, the Hg / HgO electrode as the reference electrode, the Pt sheet electrode as the counter electrode, and a 3M KOH solution as the electrolyte.

[0051] The electrochemical performance test results of Co(OH)2 / NF are as follows Figure 6 As shown, the charge and discharge are carried out in the range of 0-0.5V and the current density is 1mA cm -2 When the area specific capacitance of Co(OH)2 / NF is 2.1F cm -2 .

[0052] Step 2, preparation of nickel foam loaded ZIF-67 and cobalt hydroxide, first, dissolve 1.5g of 2-methylimidazole in 20mL of deionized water to obtain an impregnation solution, then immerse the Co(OH)2 / NF obtained in step 1 in the impregnation solution for 24h, finally, wash the impregnated NF with deionized water, and then vacuum dry it at a drying temperature of 60°C for 12h to obtain nickel foam loaded ZIF-67 and cobalt hydroxide ZIF-67@Co(OH)2 / NF;

[0053] In order to prove the composition of ZIF-67@Co(OH)2 / NF, XRD test was carried out, and the test results are shown in Figure 4. Figure 1 As shown, ZIF-67@Co(OH)2 / NF exhibits not only the characteristic peaks of Co(OH)2 but also those of ZIF-67. The test results indicate that step 2 partially converts Co(OH)2 into ZIF-67, successfully preparing ZIF-67@Co(OH)2 / NF.

[0054] In order to verify the microstructure of ZIF-67@Co(OH)2 / NF, SEM test was carried out. The test results are shown in Figure 2. Figure 3 As shown, it is clearly observed that the dodecahedral particles of ZIF-67 are relatively evenly loaded on the flaky Co(OH)2. Combined with the XRD test results, it can be seen that ZIF-67 is successfully loaded on Co(OH)2 / NF.

[0055] In order to prove the electrochemical performance of ZIF-67@Co(OH)2 / NF, the electrochemical performance test of ZIF-67@Co(OH)2 / NF obtained in step 2 was carried out. The specific method of the electrochemical performance test was as follows: the electrochemical performance test was carried out in a three-electrode system consisting of the material to be tested as the working electrode, the Hg / HgO electrode as the reference electrode, the Pt sheet electrode as the counter electrode, and 3M KOH solution as the electrolyte.

[0056] The electrochemical performance test results of ZIF-67@Co(OH)2 / NF are shown in Figure 2. Figure 6 As shown, the charge and discharge are carried out in the range of 0-0.5V and the current density is 1mA cm -2 When the area specific capacitance of ZIF-67@Co(OH)2 / NF is 7F cm -2 .

[0057] Step 3, preparation of nickel foam loaded nickel cobalt layered double hydroxide and cobalt hydroxide. First, dissolve 0.291 g of nickel nitrate hexahydrate in 50 mL of anhydrous ethanol to obtain a hydrothermal reaction solution. Then, at a hydrothermal temperature of 140°C and a hydrothermal time of 8 h, the ZIF-67@Co(OH)2 / NF obtained in step 2 is vertically immersed in the reaction solution for a hydrothermal reaction. Finally, the NF after the reaction is washed with deionized water, and then vacuum dried at a drying temperature of 60°C and a drying time of 12 h to obtain nickel foam loaded nickel cobalt layered double hydroxide and cobalt hydroxide NiCo-LDH@Co(OH)2 / NF, that is, a nickel foam-based composite material based on the electrodeposition / hydrothermal combined method, referred to as NiCo-LDH@Co(OH)2 / NF.

[0058] In order to prove the composition of NiCo-LDH@Co(OH)2 / NF, XRD test was carried out. The test results are as follows Figure 1As shown, NiCo-LDH@Co(OH)2 / NF has the characteristic peaks of NiCo-LDH, indicating that ZIF-67 was successfully hydrothermally etched into NiCo-LDH, that is, NiCo-LDH@Co(OH)2 / NF was successfully prepared.

[0059] In order to further prove the composition of NiCo-LDH@Co(OH)2 / NF, XPS test was performed. The test results are as follows Figure 4 As shown in the XPS total spectrum, the characteristic peaks of Ni, Co, O and C elements exist simultaneously, and the spectra show that NiCo-LDH@Co(OH)2 / NF contains Ni 2+ 、Co 2+ 、Co 3+ , metal hydrogen bond. The XPS test results are consistent with the XRD test, indicating that ZIF-67 is successfully converted into NiCo-LDH.

[0060] In order to verify the microstructure of NiCo-LDH@Co(OH)2 / NF, SEM test was carried out. The test results are shown in Figure 2. Figure 5 As shown in the figure, the morphology of the honeycomb structure stacked by etching ZIF-67 is shown. This special structure can provide more redox active sites, which is beneficial to improving the energy storage capacity of the electrode.

[0061] In order to prove the electrochemical performance of NiCo-LDH@Co(OH)2 / NF, the electrochemical performance test of NiCo-LDH@Co(OH)2 / NF obtained in step 3 was carried out. The specific method of the electrochemical performance test was as follows: the electrochemical performance test was carried out in a three-electrode system consisting of the material to be tested as the working electrode, the Hg / HgO electrode as the reference electrode, the Pt sheet electrode as the counter electrode, and 3M KOH solution as the electrolyte.

[0062] The electrochemical performance test results of NiCo-LDH@Co(OH)2 / NF are shown in Figure 2. Figure 6 As shown, the charge and discharge voltage range is 0-0.5 V and the current density is 1 mA cm -1 Under the conditions of 100 nm, the area specific capacitance of NiCo-LDH@Co(OH)2 / NF is 17.7 F cm -2 Compared with step 2, it can be seen that the hydrothermal etching in step 3 can significantly improve the area capacitance performance by 254%.

[0063] The cycling performance test results of NiCo-LDH@Co(OH)2 / NF are shown in Figure 2. Figure 7 As shown, at a current density of 10 mA cm -2 , NiCo-LDH@Co(OH)2 / NF retained 70.7% of its initial specific capacitance under the condition of 5000 cycles.

[0064] In order to further demonstrate the electrochemical performance of NiCo-LDH@Co(OH)2 / NF, a double electrode test was performed. Figure 8 As shown, at a power density of 7.99 mW cm -2 When the energy density of NiCo-LDH@Co(OH)2 / NF is 0.382mWhcm -2 .

[0065] By comparing step 2 and step 3, it can be seen that the NiCo-LDH obtained by etching ZIF-67 has a honeycomb structure stacking morphology. The special structure can provide more redox active sites, which is beneficial to improving the energy storage capacity of the electrode and allowing more active parts to participate in the Faraday redox reaction. Therefore, the NiCo-LDH@Co(OH)2 / NF obtained by etching ZIF-67 has excellent specific capacitance performance.

[0066] In order to demonstrate the effect of electrodeposition of cobalt hydroxide, i.e., step 1 of the preparation method, on the performance, Comparative Example 1 is provided, which is a NiCo-LDH obtained by direct hydrothermal etching of ZIF-67.

[0067] Comparative Example 1

[0068] A method for preparing NiCo-LDH obtained by direct hydrothermal etching of ZIF-67, wherein the steps not specifically described are the same as those of the preparation method in Example 1, except that step 1 is not required, and in step 3, ZIF-67 is etched with Ni(NO3)2·6H2O. The obtained material is referred to as NiCo-LDH.

[0069] The XRD test results of NiCo-LDH are as follows Figure 9 As shown, NiCo-LDH has characteristic peaks of NiCo-LDH. Compared with the NiCo-LDH obtained in step 2 of Example 1, it can be seen that the preparation method has no substantial effect on the composition.

[0070] The SEM test results of NiCo-LDH are as follows Figure 10 As shown, the microstructure of NiCo-LDH is a lamellar flower-like structure with a particle size of 2-4 μm. Compared with the NiCo-LDH@Co(OH)2 / NF of Example 1, it can be seen that the lack of the first step of electrodeposition of cobalt hydroxide causes the NiCo-LDH to agglomerate together, failing to achieve the uniform loading of Example 1.

[0071] The electrochemical performance test results of NiCo-LDH are as follows Figure 11 As shown, the charge and discharge are carried out in the range of 0-0.5V and the current density is 1mA cm -1When the mass specific capacitance of NiCo-LDH is 1348F g -1 The test results show that, compared with Example 1, the use of the electrodeposition method to prepare Co(OH)2 can significantly improve the specific capacitance performance of the composite material.

Claims

1. A nickel-based foam composite material based on an electrodeposition / hydrothermal combined method, characterized in that: Firstly, nickel foam NF was used as the substrate, and cobalt hydroxide was loaded on the NF surface by electrodeposition to obtain nickel foam electrodeposited cobalt hydroxide Co(OH)2 / NF; then, it was converted into ZIF-67 by impregnation method to obtain nickel foam electrically loaded ZIF-67@cobalt hydroxide ZIF-67@Co(OH)2 / NF; finally, a nickel foam-based composite material NiCo-LDH@Co(OH)2 / NF based on the electrodeposition / hydrothermal combined method was obtained by hydrothermal method.

2. The nickel-based foam composite material according to claim 1, wherein: The micromorphology of the Co(OH)2 / NF is a lamellar stacked flower-like structure; the micromorphology of the ZIF-67@Co(OH)2 / NF is a regular dodecahedron structure; and the micromorphology of the NiCo-LDH@Co(OH)2 / NF is a honeycomb stacked structure.

3. A method for preparing a foamed nickel-based composite material based on an electrodeposition / hydrothermal method, characterized in that The following steps are involved: Step 1, preparation of nickel foam electrodeposited cobalt hydroxide, first, dissolving cobalt nitrate hexahydrate in deionized water to obtain electrodeposition solution A, then using a two-electrode system and cyclic voltammetry, with nickel foam NF as the working electrode and a Pt sheet as the counter electrode, to perform electrodeposition under certain conditions, finally, washing the electrodeposited NF with deionized water and then vacuum drying under certain conditions to obtain nickel foam electrodeposited cobalt hydroxide Co(OH)2 / NF; Step 2, preparation of nickel foam loaded with ZIF67 and cobalt hydroxide, first, dissolving 2-methylimidazole in deionized water to obtain an impregnation solution, then impregnating the Co(OH)2 / NF obtained in step 1 in the impregnation solution under certain conditions, finally, washing the impregnated NF with deionized water, and then vacuum drying under certain conditions to obtain nickel foam loaded with ZIF-67 and cobalt hydroxide ZIF-67@Co(OH)2 / NF; Step 3, preparation of nickel foam-loaded nickel cobalt layered double hydroxide and cobalt hydroxide NiCo-LDH@Co(OH)2. First, nickel nitrate hexahydrate and urea are dissolved in anhydrous ethanol to obtain a hydrothermal reaction solution. Then, under certain conditions, the ZIF-67@Co(OH)2 / NF obtained in step 2 is immersed in the reaction solution for a hydrothermal reaction. Finally, the NF after the reaction is completed is washed with deionized water and then vacuum-dried under certain conditions to obtain nickel foam-loaded nickel cobalt layered double hydroxide and cobalt hydroxide NiCo-LDH@Co(OH)2 / NF. In the preparation method, all vacuum drying conditions are: drying temperature is 50-70° C., and drying time is 11-13 h.

4. The preparation method according to claim 3, wherein: In step 1, the conditions for the first electrodeposition are: electrodeposition potential of 5-7 V, scan rate of 90-110 mV s -1 , the electrodeposition time is 1190-1210s.

5. The preparation method according to claim 3, characterized in that: In step 2, the immersion condition is that the immersion time is 23-25 ​​hours.

6. The preparation method according to claim 3, characterized in that: In step 3, the hydrothermal conditions are as follows: the ZIF-67@Co(OH)2 / NF is immersed in a vertical manner, the hydrothermal temperature is 130-150°C, and the hydrothermal time is 7-9h.

7. The preparation method according to claim 3, characterized in that: When the obtained nickel foam composite material based on the electrodeposition / hydrothermal method is used as a supercapacitor material, it is charged and discharged in the voltage window range of 0-0.5V, and the current density is 1mAcm -2 When the area specific capacitance is 17-18F cm -2 .

8. The preparation method according to claim 3, characterized in that: The obtained nickel-based foam composite material based on the electrodeposition / hydrothermal method was used as a supercapacitor material at a current density of 10 mA cm -2 When the battery is charged and discharged for 5,000 times, it still retains 70-80% of its initial capacity.

Citation Information

Patent Citations

  • Foamed nickel loaded cobalt sulfide / nickel sulfide NF-CoS / NiS as well as preparation method and application thereof

    CN120126949A

Cited By

  • Co (OH) 2 / NiCo-LDH heterojunction catalyst and preparation method and application thereof

    CN121931565A